2004
DOI: 10.1097/01.coc.0000136019.94333.09
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Features and Survival of Inoperable Hepatocellular Carcinoma in Turkish Patients With Cirrhosis

Abstract: HCC occurred only in patients with liver cirrhosis. Survival time can be predicted from information collected by the physician at the initial assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 11 publications
2
20
1
1
Order By: Relevance
“…Portal vein thrombosis and lymph node metastasis were negative predictive factors of OS in this study. These are well known factors predicting shorter OS in HCC patients regardless of the administration of sorafenib . It has also been demonstrated by Song et al .…”
Section: Discussionsupporting
confidence: 55%
“…Portal vein thrombosis and lymph node metastasis were negative predictive factors of OS in this study. These are well known factors predicting shorter OS in HCC patients regardless of the administration of sorafenib . It has also been demonstrated by Song et al .…”
Section: Discussionsupporting
confidence: 55%
“…This can be attributed to the fact that more advanced tumours were included in this study. Portal vein thrombosis is a well‐known predictor of shorter OS in HCC patients . All the patients of the sorafenib‐treated group in the propensity score‐matched cohort had PVTT, whereas in the SHARP and Asia‐Pacific trials, only 36% of the patients had macrovascular invasion in both studies .…”
Section: Discussionmentioning
confidence: 98%
“…Several studies in patients with advanced HCC managed with non-surgical modalities have demonstrated that PVT is associated with reduced survival (25,28,29). One study in HCC patients treated with ablation, percutaneous ethanol injection, and RFA (30) used a multivariate survival analysis to demonstrate that PVT was a significant and independent negative predictor of survival.…”
Section: Discussionmentioning
confidence: 99%
“…As with other cancer-associated thromboses, the presence of PVT in patients with HCC is associated with reduced survival. (25,(28)(29)(30)(31)(32) However, little is known about factors predictive for PVT in patients with HCC. In a single autopsy study of 72 patients with HCC PVT was found in 44%, and female sex and older age were identified as predictive factors (26).…”
mentioning
confidence: 99%